Thermal Performance Enhancement for Heat Exchanger Tube Fitted with Vortex Generator Inserts. Issue 21 (1st September 2021) - Abdelmaksoud, Waleed A.; Mahfouz, Alaa E.; Khalil, Essam E.
Abstract: The aim of the present study is to numerically investigate the thermal performance of a heat exchanger tube fitted with vortex generator inserts. In the present paper, three configurations of vortex generators—straight, double-curved, and triple-curved—are proposed to achieve the optimum configuration design that provides the highest thermal performance. The thermal performance results of the tubes fitted with the proposed vortex generators are compared with those fitted with a classical twisted tape and a plain tube. The triple-curved vortex generator, which is tested at four different pitch ratios (5, 4, 3, and 2), exhibits the highest thermal performance at a low Reynolds number. The numerical results indicate that the thermal performance increases as the pitch ratio decreases. Compared with the twisted tape, if the triple-curved vortex generator is employed at a pitch ratio of 2, the thermal performance can improve by approximately 24%. Using the numerical results of the current study, dimensionless correlations for the triple-curved vortex generator are developed and presented in this paper.